392 Outcomes of Anatomical Custom Patient-Specific Implants After 3D CT Pre-Operative Planning for Complex Hip Conditions. (28th February 2022) - Petohazi, A.; Musbahi, O.; Akilapa, O.; Gee, M.; Harnett, P.
Abstract: Aim: Primary THA in complex hip conditions presents a challenge for an orthopaedic surgeon. Often, the anatomical restoration is less than ideal with an "off the shelf" implant. The use of 3D planning with customized implants is an emerging technology to meet this challenge. However, patient outcomes are unknown. In this study, we present the 1-year results of patients with complex hip conditions undergoing custom implants and 3D pre-operative planning. Method: We conducted a retrospective review of all patients that underwent 3D planning and custom Total Hip Arthroplasty implant. Demographic data and indications were collected. Operative details and postoperative complications were reviewed. Post-operative radiographic assessment and measurements were reviewed. Oxford Hip scores at 1 year were compared with national standards. Results: Sixteen patients underwent Total Hip Replacement after Symbios 3D Preoperative planning with custom made implants at 1 Major Trauma Centre. The mean age was 43 consisting of 8(50%) females and 8 males. The most common indication was hip dysplasia(5/16). Mean Operative time was 114mins(range80–200mins). Mean operative blood loss was <500ml and length of stay were 3 days. Mean Oxford Hip Scores at 1 year was 45/48. There were no signs of radiographic loosening or dislocation. Conclusions: Custom implants after 3D planning is an effective treatment for restoring anatomy and improving functional outcomes. Outcomes were comparable to national standards to patients undergoing primary total hip arthroplasty for osteoarthritis.